Ultrafast terahertz transparency boosting in graphene meta-cavities - Wang Lan; An Ning; Gong Sen; Sheng Xuan; Li Yiwei; Yao Baicheng; Yu Cui; He Zezhao; Liu Qingbin; Feng Zhihong; Otsuji Taiichi; Zhang Yaxin (Nanophotonics)
As an exceptional nonlinear material, graphene offers versatile appealing properties, such as electro-optic tunability and high electromagnetic field confinement in the terahertz regime, spurring advance in ultrashort pulse formation, photodetectors and plasmonic emission. However, limited by atomic thickness, weak light–matter interaction still limits the development of integrated optical devices based on graphene. Here, an exquisitely designed meta-cavities combined with patterned graphene is used to overcome this challenge and promote THz-graphene interaction via terahertz location oscillation. By using an 800 nm pump laser, the local field-induced strong interaction allows sensitive responses to the ultrafast energy transfer from the ultrafast optical pump to graphene electron heat, enabling 46.2% enhancement of terahertz transparency. Such optical modulation of terahertz waves shows ultrafast response in delay less than 10 ps. Moreover, thanks to the nature of graphene, the device shows unique potential for electrically dynamic tuning and further bandwidth broadening.